KAMCHATKA REGION POWER SYSTEM - I. E. Shkradyuk; И. Э. Шкрадюк (Alternative Energy and Ecology (ISJAEE), 2016)
The Kamchatka energy development strategy has relied on the use of natural gas and to a lesser extent renewable energy sources (RES) over the past 20 years. Since 2012 the Kamchatka region government has prepared HPP cascade construction on Zhupanova river. HPP development proponents refer to the experience of Iceland, which hydroelectric power plants produce three-quarters of electricity and geothermal power plants – one-quarter one. A comparison of the existing Iceland HPP and the planned cascade of Kamchatka shows that the main technical and economic parameters of HPP of Kamchatka significantly inferior to Iceland HPP. High risks as well as the high construction cost confirmed that the project is inadvisable, and it was closed. Therefore, further regional energy development depends on the RES and local fuel effective use. Стратегия развития энергетики Камчатки на протяжении последних 20 лет опиралась на использование природного газа и в меньшей степени возобновляемых источников энергии. С 2012 года правительство Камчатского края активно осуществляет подготовку к строительству каскада ГЭС на р. Жупанова. Сторонники развития гидроэнергетики ссылаются на опыт Исландии, где ГЭС вырабатывают три четверти электроэнергии, остальную четверть – геотермальные электростанции. Сравнение действующей ГЭС Исландии и проектируемого каскада ГЭС Камчатки показало, что по основным технико-экономическим параметрам ГЭС Камчатки значительно уступают ГЭС Исландии. Высокие геологические, технические, экономические и экологические риски, высокая стоимость строительства каскада ГЭС привели к решению о нецелесообразности реализации проекта. Дальнейшее развитие региональной энергетики зависит от эффективного использования разных видов возобновляемых источников энергии и других местных энергоресурсов.